Independent Commissioners, Company Size, and Financial Distress on Accounting Conservatism with Leverage as a Mediating Variable (Empirical Study on Financial Companies in the Insurance and Financing Sub-Sector Listed on the IDX 2019-2021) - Siti Ratih Nurwanti; Lia Uzliawaty; Tri Lestari (Jurnal Akuntansi, 2023)
This research is a descriptive quantitative research which is based on the condition of applying the principles of accounting conservatism in financial reports in Indonesia which still reaps pros and cons. As well as the results of previous studies regarding the influence of independent commissioners, company size and financial distress on accounting conservatism with leverage as a mediating variable, they are still inconsistent. In this study, samples were used in the form of secondary data from 25 financial companies in the insurance sub-sector and financing institutions listed on the IDX 2019 – 2021, which were obtained through the website www.idx.co.id. This study aims to determine: 1) The effect of independent commissioners on accounting conservatism. 2) The effect of firm size on accounting conservatism. 3) The effect of financial distress on accounting conservatism. 4) The effect of leverage on accounting conservatism. 5) The effect of independent commissioners on leverage. 6) The effect of firm size on leverage. 7) The effect of financial distress on leverage. 8) the influence of independent commissioners on accounting conservatism through leverage. 9) theeffect of firm size on accounting conservatism through leverage. 10) the effect of financial distress on accounting conservatism through leverage. Keywords: Accounting Conservatism, Independent Commissioner, Financial Distress, Leverage, and Company Size